Novel kinase-activating genetic events in non-small cell lung carcinomas - Elena V. Preobrazhenskaya; Rimma S. Mulkidjan; Fyodor A. Zagrebin; Alexandr A. Romanko; Evgeniya S. Saitova; Polina R. Korzun; Jeyla O. Binnatova; Vladislav I. Tiurin; Ilya V. Bizin; Evgeny N. Imyanitov (Exploration of Targeted Anti-tumor Therapy)
Aim: This study aimed at the identification of new druggable alterations in non-small cell lung carcinomas (NSCLCs). Methods: RNA next generation sequencing (NGS) analysis for 650 protein kinase genes was performed for 89 NSCLCs obtained from young-onset and/or female non-smokers, who were negative for activating events involving EGFR, ALK, ROS1, RET, MET, NTRK1/2/3, BRAF, HER2, KRAS, or NRAS genes. Results: RNA sequencing identified 32 in-frame rearrangements, including 9 instances of fully preserved and 8 tumors with partially preserved tyrosine kinase domains. These 17 translocations were further analyzed in 1,059 mutation-negative NSCLCs, which resulted in the identification of two additional tumors with ADK::KAT6B rearrangement and one carcinoma carrying RPS6KB1::VMP1 fusion. The recently reported CLIP1::LTK gene fusion was tested in 2,754 NSCLCs, which were negative for all known actionable mutations, however, no new instances of this translocation have been observed. We further analyzed RNA sequencing results of 89 NSCLCs for mutations affecting the kinase domain of the involved gene. There were 53 substitutions with a combined annotation dependent depletion (CADD) score above 25; all these lesions turned out to be unique, as the analysis of 551 additional NSCLCs revealed no recurrent alterations. ROS1, LTK, and FGFR4 high-level overexpression was observed in 1 out of 89 tumors each. Conclusions: This study demonstrates the scarcity of yet unknown kinase-activating alterations in NSCLCs.